PENGARUH PRENATAL YOGA KOMBINASI DENGAN TERAPI MUSIK KLASIK TERHADAP TINGKAT KECEMASAN IBU HAMIL PRIMIGRAVIDA TRIMESTER III DI GRIYA BUNDA CERIA PALEMBANG - Soleha, Marchatus; Aini, Apriyanti; Suryanti, Yuli (Jurnal Kesehatan Abdurrahman, 2026)
Anxiety is a physiological condition and a common experience among third-trimester primigravida pregnant womenAnxiety can be reduced or alleviated through prenatal yoga combined with classical music therapy. The purpose of this study is to determine the effect of prenatal yoga combined with classical music therapy on anxiety levels in third-trimester primigravida pregnant women. This study employed a quasi-experimental method with a one-group pretest-posttest design. The population consisted of all third-trimester primigravida pregnant women, and a sample of 10 respondents experiencing anxiety was selected. The intervention was conducted over four weeks, with a frequency of once a week and a duration of 60 minutes per session. Data were analyzed using univariate and bivariate methods, with the Wilcoxon non-parametric test. Before the intervention, most participants experienced mild anxiety (50%), while after the intervention, the majority showed mild anxiety levels (80%). The bivariate test results showed a p-value of 0.005 (< α 0.05), indicating that prenatal yoga combined with classical music therapy has a significant effect on reducing anxiety levels in third-trimester primigravida pregnant women.